SCIENTIFIC AND METHODOLOGICAL CONDITIONS OF DETERMINATION OF BUILD CLUSTER IN THE SYSTEM OF ORGANIZATIONAL AND ECONOMIC PROVIDING ENERGY SAVINGS OF THE ENTERPRISE - Doroshenko , V.M. (The actual problems of regional economy development, 2017)
In the article, based on the results of the research of the categorical and conceptual apparatus of the cluster approach, taking into account the specifics and problems of implementation of energy saving measures in construction, the author's definition of the cluster is proposed. Existing conditions for the efficient functioning of the cluster by invariance are supplemented. The scheme of determination of the construction cluster in the system of organizational and economic provision of energy saving is presented, where tendencies of incorporation of measures of energy saving in the conditions of the newest technological way are determined.